(untitled) (Research, Society and Development, 2021)
There is sufficient evidence to support a relationship between the severity of periodontal disease and COVID-19 infections. This relationship may be caused by an increase in the immune response mediated by Galectin 3 (Gal-3) and an increase in viral adhesion. Thus, unsatisfactory and poor hygiene conditions determine risk factors in the worsening of the disease. The objective of this study was to analyze the oral hygiene index in patients diagnosed with COVID-19 admitted to the ward of a referral hospital in the metropolitan region of Santa Rita (Paraíba). This study can relate oral inflammatory problems and their outcome in the evolution of patients with COVID-19, contributing to a planning of continuing education actions in oral health care, and to a better evolution of patients with COVID-19. For data collection, a google forms form was used, built by the research team, based on the Oral Hygiene Index in Critical Patients (OHICP), with modifications. In the assessment of the oral hygiene condition of patients with COVID-19, it was observed that 74.1% of the patients presented unsatisfactory and / or precarious oral hygiene. Patients with COVID-19 presented more frequently tongue coating (74.3%), visible biofilm (41.6%) and food remains (35.5%). Poor oral hygiene can aggravate clinical conditions, worsening the outcome regarding the treatment of patients with SARS-CoV-2.